Mobile Phones and Mozambique Farmers: Less Asymmetric Information and More Trader Competition? - Wouter Zant (Tinbergen Institute, 2018)
We measure the impact of search costs on farmers' and traders' transaction prices in Mozambique by investigating to what extent the introduction of mobile phones has affected the margin between recorded maize producer and retail market prices, and by exploring if producers or traders benefit from possible margin changes. Estimations are based on weekly producer and retail market prices of white maize grain, from July 1997 to December 2009, for 15 major producer markets in Mozambique. We find a margin increase that varies from 4.5% to 9.6%, supporting a bias of benefits of mobile phones towards maize traders and hence not less asymmetric information and increased trader competition, but rather the reverse. Impacts on producer and market prices independently vary, but confirm the margin results. Estimation results are robust for non-random rollout of the mobile phone network and various other threats.
Keywords: O13; O33; Q11; Q13; 330; search costs; transport costs; mobile phones; agricultural markets; maize prices; Mozambique; sub-Sahara Africa